If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + -7 + -2x = 9x + 15 Reorder the terms: -7 + 10x + -2x = 9x + 15 Combine like terms: 10x + -2x = 8x -7 + 8x = 9x + 15 Reorder the terms: -7 + 8x = 15 + 9x Solving -7 + 8x = 15 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -7 + 8x + -9x = 15 + 9x + -9x Combine like terms: 8x + -9x = -1x -7 + -1x = 15 + 9x + -9x Combine like terms: 9x + -9x = 0 -7 + -1x = 15 + 0 -7 + -1x = 15 Add '7' to each side of the equation. -7 + 7 + -1x = 15 + 7 Combine like terms: -7 + 7 = 0 0 + -1x = 15 + 7 -1x = 15 + 7 Combine like terms: 15 + 7 = 22 -1x = 22 Divide each side by '-1'. x = -22 Simplifying x = -22
| 1.5(v+10)=127.5 | | (4/x+1+2/x-1)=35/x^2-1 | | 3(6x-10)=-30 | | 4/5x+7=5 | | -5(u-4)+2=11-(u-3) | | (2+7m)+5=0 | | X+5y=90 | | 23-x=50 | | 7(-9+5x)=-133 | | 4(2x-1)-3(x-2)=10+5x | | 2a+1=5a-2/2 | | X-1/4=6 | | 3k-2=4k-4 | | (x-35)+(x-46)+x+.5x=360 | | Y+2y+15=180 | | 3(4+2x)=18-6x | | (4x^2-x)-3x^2= | | 2x+5(x-3)=x+2 | | 5-k=36 | | 34=-17w | | 63=-3y | | 12(2+7)-24/12 | | 8x+1=7x-9 | | 6(4+x)=66 | | 6x-(3X-7)=29 | | 7x-(2x-22)=67 | | 4(x-5)=5(x-4)-x | | 6x1/2y=3 | | -4/3x+7/2=-3/4x-2 | | M=9n | | 2x/3-1=x-2/2 | | 5(2ab)= |